Gender stereotype and hostile sexism among young korean gamers based on teammate selection strategy and game style preferences - Doo Heon Song; Hae Kyung Rhee; Jeong Hoon Kim (Institute of Advanced Engineering and Science, 2020)
Female gamers are growing rapidly worldwide especially in young age groups and in mobile platform. Since that population change appears in recent 10 years, formerly male-oriented gaming community has confronted gender issues. In this paper, we witness that a strong gender stereotype exists for both genders in Korea by two surveys. In the first survey, subjects show that they have different expectations of opposite gender’s favorable game style where both genders have exactly same favorite styles. In the second survey, we investigate how members of hostile sexism community groups choose teammates in Overwatch game if they have privilege to select teammates for specific roles. Ilbe and Womad as two far extreme misogyny and misandry groups show hostile sexism in teammate selection. The result implies that hostile sexism and gender stereotype shown in game playing may be induced from other social factors than the amount of the game playing experiences.